An explorative study of discipline-specific reorganization of assessment during educational emergency – An Italian case - Eradze Maka; Tinterri Andrea; Dipace Anna; De Martino Delio (Research on Education and Media)
A coronavirus disease (COVID)-related educational emergency is believed to have changed some of the aspects of the educational landscape. Sudden changes to traditional structures that are schools are undoubtedly an interesting issue to explore: complex phenomena such as assessment methods are highly related to many different factors such as normative base, the use of technological tools, etc. This article reports on the reorganization of assessment methods in the context of a rapid and forced transition to remote teaching mode, based on the results of a survey of Italian teachers. Findings indicate that pandemic-related educational emergency and the push toward the use of tools in teaching and learning practices, and the corresponding relaxation of certain established frames of operation, have created grounds for alternative forms of assessment. Results show that when entertaining different options and enjoying some level of autonomy, teachers can explore alternative forms of assessment. Assessment methods also change according to school subjects; while assessment changes are discipline specific, there is a clear trend toward product-based assessment.